SKILLS LEARNING COMPETENCY OF THE SECONDARY SCHOOL STUDENTS IN THE PHYSICS LABORATORY - Iqbal Shah, (PJE, 2023)
Practical skills occupy a pivotal position in the laboratory teaching learning process. Developing the practical skills in the students is a very common objective of teaching Physics. Laboratories are one of the characteristic features of education in the sciences at all levels. It would be rare to find any course in any institution of education without a substantial component of laboratory activity